Toad of Toad Hall a play from Kenneth Grahame's book - Milne, A. A. (Alan Alexander) 1882-1956 (The Willow leaf library, 1957)
A four act play, based on the comedy in Kenneth Grahame's The Wind in the Willows, telling of the escapades of Toad, Mole, Rat and Badger along a river in the English countryside.